A multidimensional high-resolution assessment approach to boost decentralised energy investments in Sub-Saharan Africa. (September 2021) - Moner-Girona, M.; Bender, A.; Becker, W.; Bódis, K.; Szabó, S.; Kararach, A.G.; Anadon, L.D.
Abstract: There are over 650 million people in Africa who have no access to electricity; this is in sharp contrast to the continent's vast untapped renewable energy potential and due largely to the historical lack of investments in energy infrastructure. New investments in decentralised power generation within Sub-Saharan Africa play a progressively important role in increasing energy access and addressing the continent's electricity supply shortages. Tracking the performance of Sub-Saharan African countries along various socio-political and economic axes can spur the mobilisation of private, public and international sectors in investing in decentralised energy technologies. An increasing amount of high-resolution global spatial data are available, and used for various assessments. However, key multidimensional indicators are mainly still provided only at the national level. To this end, we present a comprehensive and consistent analysis of the attractiveness for decentralised photovoltaic technologies at an unprecedented level of detail using both high-resolution spatial data and national reports. We develop and build a new composite indicator that considers the interplay between social, political, environmental and financial factors at a granular regional level for Sub-Saharan Africa and embeds within it the importance of the local production costs at high-spatial resolution. Highlights: Composite indicator for directing/informing decentralised renewable energy investment in Sub-Saharan Africa. Integrates technological, environmental, social, political and financial factors for decision support. Combines country level data with high-spatial resolution (i.e. electricity production costs). Raw data provision enabling stakeholders to focus on specific country attributes. Interactive tool will enable users to weight indicators to their specifications.